Contribution to better understanding of logistics - Milenkov, Marjan A.; Dronjak, Milan Ž.; Parezanović, Vladan D. (Vojnotehnički glasnik / Military Technical Courier, 2015)
There are a number of definitions of logistics and logistics systems through which different authors, at different times and military, economic, market and social circumstances, tried to explain the essence of logistics as a branch of the art of war, business philosophy, scientific discipline, etc. Although logistics ia a very old area of human activity, which was improving along with the development of civilisation, its terms are still in the process of developing and they should be accepted as they appear and how they appear in different human activities. Introduction A number of businessmen still describe logistics and its activities in an abstract way, as one kind of a “blackbox“. This level of abstraction is unjustified and undesirable from the standpoint of the efficiency and efectiveness of such activities. In order to avoid abstraction, this paper attempts to contribute to a better understanding of the essence of logistics through the presentation of different approaches in determining the existing concepts and terminology, and thus make easier their further analysis in term of content, scope, characteristics, connections, complementarities, interdependance, etc. Evolution of the term „logistics“ In scientific and professional literature, there are different attitudes and approaches regarding the origin of the term „logistics“. All of them are generally correct concerning the possibility to interprete logistics as an ambiguity term. Historically, the term logistics is linked to the military, mathematical and business use. The origin of the military use of this term was related to the ancient states and Byzantium. However, Antoine-Henri Jomini is considered as the author of the first scientific papers related to military logistics in the classic sense. In his monumental work "Review of the art of war", published in 1837, he stated that the art of war is generally composed of five purely military branches: strategy, great tactics, logistics, artillery and engineering skills and detailed tactics. In addition to the intensive use of the term "logistics" in the military terminology in XIX and early XX century, in the second half of the XX century logistics entered all economic activities of the civil sector. From the standpoint of business (civil) logistics, the logistics point is determined by seven rules ("7R" - Seven Rights). The development and definition of military logistics The advanced thinking of Baron Zomini, based on the analysis of Napoleon’s wars, largely influenced other military philosophers. For example, Admiral Alfred Mahan accepted the term logistics and introduced it to the dictionary of the USA Navy. During World War II, this term was already widely used and it appeared in nearly all articles with a military theme. After World War II, this term was formally introduced in the armed forces of the United States through the release of FM 100-10. The next big step forward was made under the direction of Secretary of Defense Robert S. McNamara (1961 – 1968), when the different elements, activities and operations in logistics processes were separated in accordance with the settings of a system analysis which used the methods and techniques from the business world (statistical methods, operational research, systems analysis, etc.) and included civilian experts. Previously independent logistic services were connected within the logistics function at the level of the Ministry of Defence, in order to become more efficient and to reduce costs and make a better logistics organization. For NATO, logistics is defined as a science, in the same way as it was done in the doctrine of the armed forces of Great Britain. As for military logistics in our country, it was mainly developed empirically, while the theory was very little given a thought. The development and definition of business (civil) logistics The assumption of the logistics principles from the military sphere into the business area, has led to a widespread use of the term in the modern control theory. Using the adjective commercial (civil) is not done only to make a terminological distinction in regard to military logistics, but also to put the emphasis on logistics activities that are carried out within one business system. So, today it is considered that logistics is a modern business function used to identify, provide, monitor and control the necessary resources of the business system in the broadest sense of that word. From the business logistics point of view, logistics definitions can be classified into three groups. The definition of the logistics system Different systems were developed in order to realize logistics activities, and in the literature and operational practices they are named systems of logistics, logistics systems, support systems or system of logistical support. The logistics system is essentially a subsystem of a wider system and as such must comply with other subsystems and subordinate purpose of functioning of the wider system. There are different classifications of logistics systems in the literature, such as general, specialized, open, closed, centralized, decentralized, etc. In addition, some authors divide them into micro, macro and global logistics systems. Logistics Systems by their nature belong to complex and dynamic systems characterized by multi-dimensionality and the presence of a large number of different elements, material and immaterial flows,  subjected to constant changes and modifications. These systems are characterized by a multitude of specific constraints, elements and processes that simultaneously interact to achieve the goal. During its life cycle, every logistics system has clear organizational and technological profiled phases of executing specific tasks, achieving results and defining objectives. Logistics tasks are characterized by spatial, temporal and organizational and technological dimensions. Conclusion The main objective of logistics is to improve the overall quality, to minimize total costs and to maximize profit. These are two opposing demands, which just shows the complexity of the area and the issues dealt with logistics. Due to the complexity and presence of logistics in all areas of social life, this paper puts an emphasis on clarifying the use and the development of the term logistics in military and in business (civil) organizations, as well as on a contibution to a better understanding of the logistics system in particular.
Keywords: logistics; military logistics; business logistics; logistics system